Mother and Child Health Care Implementation during COVID-19 Pandemic - Eka Mishbahatul Mar'ah Has (Indonesian Journal of Community Health Nursing, 2020)
Tunaikan Layanan Kesehatan Ibu dan Anak di Masa Pandemi Covid-19